1987
DOI: 10.1258/002367787781268792
|View full text |Cite
|
Sign up to set email alerts
|

Airborne-induced experimental Bordetella bronchiseptica pneumonia in Strain 13 guineapigs

Abstract: SummaryTo evaluate the efficacy of a commercial bacterial vaccine in protecting Strain 13 guineapigs against fatal Bordetella bronchiseptica pneumonia, it was necessary to establish the infectivity and disease pathogenesis induced by virulent organisms. When guineapigs were exposed to small-particle aerosols of varying concentrations of virulent B. bronchiseptica, a spectrum of disease was produced that ranged from inapparent illness to fulminant bronchopneumonia. Clinical signs began by day 4 after exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Most experience over the last 90 years has been gained by the study of domesticated animals living in closed quarters. Transmission from animal to animal is by direct contact with respiratory secretions, fomites, and perhaps by aerosol (23,765). Porter et al have shown that the organism can grow in lakewater, which suggests that B. bronchiseptica may occur as a free-living organism (632,633).…”
Section: B Bronchiseptica Epidemiologymentioning
confidence: 99%
“…Most experience over the last 90 years has been gained by the study of domesticated animals living in closed quarters. Transmission from animal to animal is by direct contact with respiratory secretions, fomites, and perhaps by aerosol (23,765). Porter et al have shown that the organism can grow in lakewater, which suggests that B. bronchiseptica may occur as a free-living organism (632,633).…”
Section: B Bronchiseptica Epidemiologymentioning
confidence: 99%
“…Whereas guinea pigs of all ages are susceptible to infection, young or stressed animals are more likely to show classic signs. The organism may be readily transmitted by the airborne route 85 and by direct contact or on fomites. Pets of other species, such as rabbits, cats, and dogs, may act as the source of infection for guinea pigs within a household.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…Transmission is by fine particle aerosol onto the respiratory mucosa, by contaminated fomites, or by genital contact (Nakagawa et al, 1971;Trahan et al, 1987). The potential for transmission of Bordetella sp.…”
Section: A Bordetella Bronchisepticamentioning
confidence: 99%